Selenium Intake and Glycemic Control in Young Adults With Normal-Weight Obesity Syndrome - Santos, Acsa de Castro; Passos, Anna Flavia Ferreira; Holzbach, Luciana Carla; Cominetti, Cristiane (Frontiers in Nutrition, 2021)
Numerous endogenous functions related to antioxidant processes, reproduction, and thyroid metabolism, as well as actions related to glycemic control, have been attributed to selenium. This study aimed to evaluate whether dietary selenium consumption is associated with variables of glycemic control in a sample of young Brazilian adults with Normal-Weight Obesity (NWO) syndrome. This was a cross-sectional study that evaluated 270 individuals with adequate body weight and excess body fat, who had their body composition assessed by dual-energy X-ray absorptiometry. Socioeconomic, health, and lifestyle questionnaires and three 24-hour food records were applied. Glycemic control markers were also evaluated. The prevalence of inadequate selenium intake was analyzed by the Estimated Average Requirement (EAR) cut-point method. The prevalence of disturbances in glycemic control markers according to selenium consumption was compared by either the chi-square or the Fisher's exact test, with individuals classified according to the EAR values for selenium. The associations were evaluated by multiple linear regressions, using the backward strategy. The mean ± standard deviation (SD) age was 23.7 ± 3.3 years, and the mean ± SD daily selenium intake was 59.2 ± 26.4 µg. The overall prevalence of inadequate selenium intake was 59.2%. Individuals with selenium intakes below the EAR (≤45 µg/day) showed higher concentrations of glycated hemoglobin (HbA1c) (P = 0.002) and a higher prevalence of disturbances in HbA1c than those with selenium intakes above the EAR (>45 µg/day) (P = 0.001). Dietary selenium intake was directly associated with female sex (β = 19.95, 95% CI 5.00 to 34.89; P = 0.001) and weight (β = 6.69, 95% CI 0.56 to 12.81; P = 0.010), and inversely associated with the percentage of total body fat (β = -0.80, 95% CI -1.56 to -0,04; P = 0.010) and HbA1c (β = -7.41, 95% CI -13.06 to -1.75; P = 0.010). Considering the noticeable young age of the individuals evaluated and the high frequency of disturbances in HbA1c concentrations in those with selenium consumption below the recommendation, it is suggested that adequate dietary intake or supplementation of this micronutrient should be guaranteed to prevent future possible complications associated with glycemic control disturbances.